The biochemistry and evolution of the dinoflagellate Nucleus - Gornik, Sebastian G. (Microorganisms, 2019)
Dinoflagellates are known to possess a highly aberrant nucleus—the so-called dinokaryon—that exhibits a multitude of exceptional biological features. These include: (1) Permanently condensed chromosomes; (2) DNA in a cholesteric liquid crystalline state, (3) extremely large DNA content (up to 200 pg); and, perhaps most strikingly, (4) a deficit of histones—the canonical building blocks of all eukaryotic chromatin. Dinoflagellates belong to the Alveolata clade (dinoflagellates, apicomplexans, and ciliates) and, therefore, the biological oddities observed in dinoflagellate nuclei are derived character states. Understanding the sequence of changes that led to the dinokaryon has been difficult in the past with poor resolution of dinoflagellate phylogeny. Moreover, lack of knowledge of their molecular composition has constrained our understanding of the molecular properties of these derived nuclei. However, recent advances in the resolution of the phylogeny of dinoflagellates, particularly of the early branching taxa; the realization that divergent histone genes are present; and the discovery of dinoflagellate-specific nuclear proteins that were acquired early in dinoflagellate evolution have all thrown new light nature and evolution of the dinokaryon.